ANALISIS PENGARUH DIMENSI KOMITMEN ORGANISASI (AFFECTIVE, CONTINUANCE, NORMATIVE)TERHADAP KINERJA KARYAWAN - Nurrofi, Akhmad (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2013)
This research analyzes the influences of organizationalcommitment toemployee performance. Respondents of this research are 130 Respondent areproduction staff in XYZfirm Semarang. This research use StructuralEquitation Modeling (SEM) under AMOS 21 program as analysis toolsThe model of relationship between the three variables studied shownthat the organizational commitment that comprise of affective commitment,continuance commitment, have a significant effect on employee’s performancewith positive signs. The studied also shown that normatif commitment, haveno significant effect on employee’s performance.